2015
DOI: 10.1364/ol.40.000221
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and control of surface plasmon resonance sensitivity using grating in conical mounting configuration

Abstract: In this work we propose a method to enhance and control the angular sensitivity of a grating coupled surface plasmon resonance (GCSPR) sensor. We lighted a silver grating, mounted in conical configuration, with a laser source and we measured the transmittance of the grating as a function of the azimuthal angle. To evaluate the sensitivity, grating surface was functionalized with four different alkanethiol self assembled monolayers (SAM) and the correspondent azimuthal transmittance peak shifts were measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The EC-SPR measurements were performed using a BI-3000G SPR Instrument (Biosensing Instrument Inc., USA), which enabled the real-time monitoring of the index of refraction at a resolution of <10–8 units, and angular modulation down to <10–5 degrees for a 690 nm wavelength light source. 40 The electrochemical reduction of the GO films was performed in a 2 ml internal sample volume cell using a CHI-604D electrochemical analyzer work station (CH Instruments Inc., Austin, TX, USA) for the three-electrode system including the modified Au electrode as the working electrode, platinum (Pt) wire as the counter electrode, and Ag/AgCl (saturated KCl) as the reference electrode. PL measurements were performed using a 405 nm diode laser at 30 mW (Tayhwa Technology Co., Ltd., Taiwan) and a high resolution spectrometer (HR 2000+, Ocean Optics, Inc., USA) at a fixed incident angle for the normal (0°) angle and spectrometer at 45°.…”
Section: Methodsmentioning
confidence: 99%
“…The EC-SPR measurements were performed using a BI-3000G SPR Instrument (Biosensing Instrument Inc., USA), which enabled the real-time monitoring of the index of refraction at a resolution of <10–8 units, and angular modulation down to <10–5 degrees for a 690 nm wavelength light source. 40 The electrochemical reduction of the GO films was performed in a 2 ml internal sample volume cell using a CHI-604D electrochemical analyzer work station (CH Instruments Inc., Austin, TX, USA) for the three-electrode system including the modified Au electrode as the working electrode, platinum (Pt) wire as the counter electrode, and Ag/AgCl (saturated KCl) as the reference electrode. PL measurements were performed using a 405 nm diode laser at 30 mW (Tayhwa Technology Co., Ltd., Taiwan) and a high resolution spectrometer (HR 2000+, Ocean Optics, Inc., USA) at a fixed incident angle for the normal (0°) angle and spectrometer at 45°.…”
Section: Methodsmentioning
confidence: 99%
“…The SPR measurements allow rapid, sensitive, real-time, and label-free analysis, and they can also be applied in an array to detect analytes simultaneously [14]. SPR measurements are typically carried out by using two configurations: the prism-coupled SPR, also called Kretschmann configuration [15], and the grating-coupled configuration [16][17][18][19][20]. In the Kretschmann configuration, a high refractive index prism is exploited in order to increase the incident light momentum and achieve the SPP-momentum matching [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus essential to find strategies to enhance the sensitivity of these sensors. It was demonstrated that a sensitivity enhancement can be achieved by working in “conical mounting,” a configuration where the scattering plane is rotated of an azimuthal angle with respect to the grating wave vector [ 25 , 26 , 27 , 28 ]. It was also observed that the symmetry breaking, due to the azimuthal rotation, involves a fundamental role of the incident light polarization on SPP excitation [ 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%